2019
DOI: 10.1101/2019.12.18.867333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

VPS41recessive mutation causes ataxia and dystonia with retinal dystrophy and mental retardation by inhibiting HOPS function and mTORC1 signaling

Abstract: The vacuolar protein sorting protein 41 (VPS41) is a neuroprotective protein in models of Parkinson's disease (PD). As part of the HOPS (Homotypic fusion and Protein Sorting) complex, VPS41 regulates fusion of lysosomes with late endosomes and autophagosomes. Independent of HOPS, VPS41 regulates transport of newly synthesized lysosomal membrane proteins and secretory proteins. Here we report two brothers with compound heterozygous mutations in VPS41 (VPS41 R662* and VPS41 S285P ), born to healthy and non-consa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…Corroborating our findings, we note that a paper not yet published but recently deposited with bioRxiv describes an additional family where 2 siblings with homozygous missense variants in VPS41 were affected by dystonia and ataxia, with similar MRI findings to our proband, and lysosomal abnormalities in patient-derived fibroblasts. 16 Thus, our study further supports the emerging role of biallelic LOF VPS41 mutations in early-onset movement disorders. The microscopic vacuolar changes we observed in both VPS16 and VPS41-patient-derived cells are consistent with lysosomal dysfunction.…”
Section: Discussionsupporting
confidence: 81%
“…Corroborating our findings, we note that a paper not yet published but recently deposited with bioRxiv describes an additional family where 2 siblings with homozygous missense variants in VPS41 were affected by dystonia and ataxia, with similar MRI findings to our proband, and lysosomal abnormalities in patient-derived fibroblasts. 16 Thus, our study further supports the emerging role of biallelic LOF VPS41 mutations in early-onset movement disorders. The microscopic vacuolar changes we observed in both VPS16 and VPS41-patient-derived cells are consistent with lysosomal dysfunction.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, HA-VPS41 S284P –expressing cells displayed a defect in EGF degradation similar to VPS41 KO cells, indicating a defect in HOPS ( Fig. 2 B ) as observed in other cell types ( 20 ). Strikingly, we observed that this mutant rescued insulin secretion and insulin content ( Fig.…”
Section: Resultsmentioning
confidence: 68%
“…We also find that the S285P human mutation, which is unable to rescue HOPS function ( 20 ), restores insulin secretion completely, indicating that it is actually possible to isolate HOPS-dependent and -independent functions of VPS41. Furthermore, this observation also helps explain why patients bearing this mutation have no observable endocrine-associated defects.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations